ANALISIS KETELITIAN GEOMETRIK MESIN FRAIS HORISONTAL KUNZMANN UF6N DI LABORATORIUM MANUFAKTUR TEKNIK MESIN UNSRAT - Krisnal Tolosi; Rudy Poeng; Romels Cresano Apelles Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
This study aims to determine the feasibility of operational a of machine tools through the static testing based on the geometric characteristics of the ISO-1710 standard, with a case study on a horizontal milling machine type of UF6N Kunzmann's in Mechanical Engineering Manufacturing Laboratory of University of Sam Ratulangi (UNSRAT). Testing includes the table alignment, the vertical motion knee alignment, the arbor with table alignment and the deviations of spindle rotation.Test results will be compared with the permitted value according to ISO-1710 standards. The results show that the magnitude of the deviation values ​​obtained from the milling machine is not meet the standard to produce a high accuracy product, but the machine is applicable for practicums of manufacturing process. Keywords: Geometric Accuracy, Machine Tools